Aplicación del “Método didáctico por descubrimiento” para mejorar el aprendizaje innovador en los alumnos del 2° grado de secundaria, área CTA – de la I.E N° 00925 “Santa Isabel” - Carbajal Lagos, Respen (2010)
The "Educational Method for Discovery" is a proposal to improve the traditional teaching, with active content and methodology in the process education teaching - learning, befare theory and teaching practice, thus achieving student's innovative learning. The objective of this research was: Developing the "Teaching and Discovery. Method" to improve innovative learning in the students CTA-Area Physical World, Technology and Environment of the lEN ° 00925 "Santa Isabel" - New Cajamarca. The "Didactic Method by Discovery", has as theoretical sustenance, to the social cognitive Theory of the learning Bandura, psychogenetic theory of Piaget, sociocultural theory of Vigotsky, theories of the significant learning of David Ausubel, theory of the learning by discovery of Bruner, theory of the information processing of Gagné, and that supported by these theories hipotetizo the following thing: lf we applied the "Didactic Method by Discovery" it will improve significantly learning innovated in the student's of the 2do.grado one of secondary Educational C.T.A- Area living Physical, Technology and Atmosphere of 00925 l. E "Santa Isabel"- New Cajamarca. The investigation design was cuasi experimental with pre-test and pos-test; with two groups experimental and control, these groups were intact nonequivalent. The sample was confirmed by 48 student's, 24 (G.E.) and 24 (G.C). The Didactic Method by Discovery development during the second trimester, obtaining to validate our hypothesis of investigation, according to demonstrates the statistical results to it where calculated T (te= 16.39) is greater than tabulate T (tt = 1.679), managing itself to accept the hypothesis of investigation (H1), which means that the average of the innovating learning of the students in postest of the experimental group (X=15,04) is superior to pos-test of the group control (X=3,29), that is to say, that the application of the "Method Didactic by Discovery" significantly improved the level of the innovating learning of the student's of 2do degree of secondary Educational area C.T.A- Living Physical, Technology and Atmosphere of the I.E. N° 00925 "Santa Isabel" - New Cajamarca.